Damage tolerance of carbon/flax hybrid composites subjected to low velocity impact. (15th April 2016) - Sarasini, Fabrizio; Tirillò, Jacopo; D'Altilia, Simone; Valente, Teodoro; Santulli, Carlo; Touchard, Fabienne; Chocinski-Arnault, Laurence; Mellier, David; Lampani, Luca; Gaudenzi, Paolo
Abstract: Hybrid laminates produced using carbon (C) and flax (F) fibre epoxy prepregs were fabricated with two different stacking sequences based on the presence of flax fibre laminates as outer layers and carbon as inner layers (FCF) or vice versa (CFC). Pure flax and pure carbon fibre reinforced laminates were also fabricated as a reference. Experimental tests were performed, which included four-point bending, falling weight impact tests at energies ranging from 5 to 30 J with determination of the barely visible impact damage (BVID) and post-impact flexural tests. As a whole, CFC proved slightly superior to FCF as for flexural performance, although the presence of flax laminates on the outside guaranteed a higher impact damage tolerance, acting as hindrance to crack propagation in the laminate. Specimens impacted at 10 J were also subjected to tensile tests monitored by Digital Image Correlation (DIC) that allowed preliminary identification of peculiar failure modes of the hybrid laminates.